MENINGKATKAN KEKUATAN OTOT TUNGKAI MELALUI LATIHAN SQUAT - Ika Sartika; Abdul Rasyid (Indonesian Journal Of Physical Activity and Sport Development (IJPASD), 2023)
Squat exercises have a significant effect on increasing strength. Squat exercises will affect the gluteus, gastrocnemius, quadriceps, hamstring, and hip flexor muscles. Basic squat exercise to develop strength in the legs and groin. This research is a quasi-experimental research with a